Deletion Analysis of the Sinorhizobium meliloti Genome - Milunovic, Branislava (My University, 2011)
The Sinorhizobium meliloti genome consists of 6204 predicted protein-coding regions of which approximately 2000 are proteins of unknown function (PUFs). To identify functions of S. meliloti PUFs, we employed the FRT/Flp recombination system to delete large gene clusters and then screened for phenotypes. Large-scale deletions have been mainly used to define minimal gene sets that contain only those genes that are essential and sufficient to sustain a functioning cell. To adapt FRT/Flp for use in S. meliloti, we used an already constructed pTH1522-derived integration gene library of the S. meliloti genome (pTH1522 carries a single FRT site). A second FRT site was inserted at defined locations in the genome through integration of a second plasmid (pTH1937) that also carries a single FRT site. Here we outline how this Flp/FRT system was used to delete defined regions and hence generate multiple gene knock-out mutants. This system was used to delete 32 and 56 defined regions from the 1340 Kb pSymA and 1678 Kb pSymB megaplasmid, respectively. The structures of the resulting megaplasmid deletion mutants were confirmed by PCR analysis. Carbohydrate and nitrogen utilization phenotypes were associated with the deletion of specific regions. Deleting large, regions of the genome helped us to identify phenotypes such as inability to grow on minimal media with fucose, maltotriose, maltitol, trehalose, palatinose, lactulose and galactosamine as sole carbon source. For several FRT-flanked regions, few or no recombinants were recovered which suggested the presence of essential genes. Through this strategy, two essential genes tRNAarg and engA located on the pSymB and three toxin/antitoxin-like systems, sma0471/sma0473, sma2105 and sma2230/sma2231 on pSymA megaplasmid were identified.
Keywords: Sinorhizobium meliloti; Flp/FRT recombination system; megaplasmids; essential genes; toxin antitoxin systems; Molecular genetics; Molecular genetics